Pengaruh Ukuran Partikel dan Laju Alir Terhadap Penyerapan Ion Zn(II) Menggunakan Kulit Langsat (Lansium domesticum) sebagai Biosorben - Lestari, Kardina; Kurniawati, Desy; Alizar, Alizar; Putra, Ananda (Departemen Kimia FMIPA UNP, 2024)
Zn2+ is a harmful ion generated from industrial waste that must be overcome. Zn (II) absorbed in excess conditions can interfere with body health and cause system dysfunction. Metal ion absorption is carried out using langsat fruit peel biosorption. Langsat fruit peel contains active functional groups that have the potential as a binding agent for Zn2+ metal ions. This study aims to determine the optimum conditions for the absorption of Zn2+ ions using langsat fruit peel on the effect of particle size and flow rate on the column. the results showed that the biosorbent was able to absorb Zn ions of 12.2994 mg/g at a particle size of 106 micro and 12.6275 mg/g at a flow rate of 1 ml/min. this shows that langsat fruit peel is one of the best biosorbents in absorbing metals with large absorption capacity data.